Penggunaan Platform Dijital Dalam Pembelajaran Penulisan Deskripsi Untuk Siswa Sekolah Dasar Tinggi - Ode Alumu, WA Ode Murima La; Gey, Masayu (Jurnal Ilmiah Wahana Pendidikan, 2025)
Enhancing the effectiveness of the teaching and learning process relies heavily on instructional media. Platform digital, which may be used to support writing skillsespecially descriptive writingis one type of learning media that is swiftly developing in the digital age. Particularly on students in the upper grades, this study hopes to investigate the impact of digital platform adoption on descriptive writing abilities of elementary school pupils. The approach employedisa literature study that analyses a range of previously reported findings retrieved via the Google Scholar data bases panning publications from 2019 to 2025.Research results show that digital platform shelp toimprove descriptive writing skills. The validity, practice, and efficacy discovered in the reviewed research support this hypothesis. Visually and interactively, platforms like Google Cardboard andPicsArt have been shown to simplify the delivery of material, hence making the learning process more interesting and pertinent. Therefore, since it fosters meaning ful learning experien cessuitab lefort here quirementsof 21st-century education, digital platforms are regarded appropriate as alearning media forimproving descriptive writing abilities in elementary school students